Consumer perceptions and attitudes toward local honey in Sabah - Ismail, Mohd Mansor; Radam, Alias; Abd. Manap, Kamsiah@ Aiidah (Universiti Putra Malaysia, 1994)
Analysing consumers perception is one way to determine whether or not local honey can fulfill the varied needs of its customer.". Using factor analysis the perception patterns of honey consumers have been grouped into 5 topical aspects namely honey characteristics, regulation, brand loyalty, freshness and honey properties. Consumers prefer local honey base Oil its characteristics. its freshness and its properlies. Regulation is needed to ensure that local honey is fresh and pure. Imported honey has created brand loyalty among consumers because of its availability, pricing and consistency ill branding,